Self Disclosure Virtual Communication in Long Distance Relationship (LDR) Couple in Managing Relationships - Martina Piranti (Universitas Medan Area, 2023)
Good communication is the key to every relationship. Long distance relationships have many challenges and require a great deal of effort between partners. Couples who, from the start of acquaintance, dating to marriage, are always separated by geographical distance, will need more time to open up. This study aims to examine how couples who are in long-distance relationships from dating to marriage manage relationships and how LDR couples use virtual communication with video calls as a communication medium. Researchers used qualitative research with the theory of Social Penetration put forward by Altman and Taylor to explore how long-distance partners open themselves to their partners. The results of this study show how important the intensity and quality of communication is in a relationship. Intense and quality communication over time leads to deeper recognition, builds trust, and reduces longing between partners. Whatsapp is a choice of communication media that is considered the most useful in channeling emotions and feelings of longing when communicating.